Genomic evidence reveals intraspecific divergence of the hot‐spring snake (Thermophis baileyi), an endangered reptile endemic to the Qinghai‐Tibet plateau. Issue 6 (19th September 2022) - Yan, Chaochao; Song, Meng‐Huan; Jiang, Dechun; Ren, Jin‐Long; Lv, Yunyun; Chang, Jiang; Huang, Song; Zaher, Hussam; Li, Jia‐Tang
Abstract: Understanding how and why species evolve requires knowledge on intraspecific divergence. In this study, we examined intraspecific divergence in the endangered hot‐spring snake ( Thermophis baileyi ), an endemic species on the Qinghai‐Tibet Plateau (QTP). Whole‐genome resequencing of 58 sampled individuals from 15 populations was performed to identify the drivers of intraspecific divergence and explore the potential roles of genes under selection. Our analyses resolved three groups, with major intergroup admixture occurring in regions of group contact. Divergence probably occurred during the Pleistocene as a result of glacial climatic oscillations, Yadong‐Gulu rift, and geothermal fields differentiation, while complex gene flow between group pairs reflected a unique intraspecific divergence pattern on the QTP. Intergroup fixed loci involved selected genes functionally related to divergence and local adaptation, especially adaptation to hot spring microenvironments in different geothermal fields. Analysis of structural variants, genetic diversity, inbreeding, and genetic load indicated that the hot‐spring snake population has declined to a low level with decreased diversity, which is important for the conservation management of this endangered species. Our study demonstrated that the integration of demographic history, gene flow, genomic divergence genes, and other information is necessary to distinguish the evolutionary processes involved in speciation.